Nanoparticles as a Delivery System for Conventional drugs and Herb-Derived Compounds for Cancer Therapy - Omar, Abdifetah Ibrahim; Muhamad, Nadda; Plengsuriyakarn, Tullayakorn; Na-Bangchang , Kesara (Challenges and Advances in Pharmaceutical Research Vol. 3, 2022)
The objective of the article is to examine the application of pharmacokinetic studies of nanoparticles loaded in conventional drugs and herb-derived compounds for cancer therapy. Several herbal remedies and chemotherapy medications incorporated into nanoparticles had their pharmacokinetic properties described. This included area under the curve (AUC) of plasma concentration-time profile, maximum plasma concentration (Cmax), time to maximum plasma concentration (Tmax), volume of distribution (Vd or Vss), elimination half-life (t ½), and clearance (CL). The systematic review was carried outusing the databases of PubMed and Science Direct until February 2019. Polymeric nanoparticles were the most widely utilized nanocarrier to improve pharmacokinetic characteristics, according to this systematic review. Nanoparticles as a novel drug delivery technology have the potential to improve the pharmacokinetics and cytotoxicity of loaded drugs/herb-derived compounds for cancer therapy.